The spending habits among ACIS students based on Dharuriyyah Concepts according to Maqasid Syariah / Ezzah Nur Akhfa Zakaria - Zakaria, Ezzah Nur Akhfa (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
This study was done in order to identify the spending habits among students of Academy of Contemporary Islamic Studies (ACIS) at UiTM Puncak Alam, Selangor, based on maqasid Syariah according to dharuriyyah concepts. The objective of this study is to determine the level of financial literacy among ACIS students. Then, to study the factors that influences their spending habits, and to find out the result of spending habits based on dharuriyyah concepts. The methodology used to collect all the data was questionnaire. From this study, the researcher has selected students of Academy of Contemporary Islamic Studies (ACIS) at UiTM Puncak Alam as respondents for this study. Thus, random technique was used by researcher to conduct this study because the population of this study consist of two courses. Around 100 questionnaires were distributed, only 80 questionnaires were collected from them. Therefore, the total of respondents of this study are 100 respondents and the certain of students from diploma in muamalat and halal management has participated in this study. Based on the study, the majority of the respondents at Academy of Contemporary Islamic Studies were female with the result; 58.8%. majority of them were students of diploma in muamalat 52.5% and the most income that students have receive is from parents; 57.5%. Besides that, majority of respondents in overall of ACIS students at UiTM Puncak Alam have receive almost RM201-RM300 with the percent of 32.5% per month. Besides, the features of products that they seek were personal satisfaction with 28.8%. the majority of 71.3% of ACIS students also prefer eat at university’s café. From the finding of the study, it can be summarized that most of 17.5% of respondents have high level of financial literacy and always follow the financial knowledge while spending. Only 12.5% of them were never plan their expenses and the most of respondents with 33.8% were often spent in their financial budget. Hence, it can be said that the overall result of the respondents was still in moderation and they were spent according to dharuriyyah and in the level of their abilities. Based on the result of the study, the researcher made up several recommendations in encouraging the use of budgeting diary and make a proper financial planning by their own to manage their income. Then, student also able to know their cash and money flow by preparing any written and electronic record of income, so that they can make improvement of their spending pattern and their financial savings. The students should to join any financial classes to monitor every spend ing they made. Lastly, for future study, the researcher has suggested to use the larger population and sample size in order to enhance the accuracy of findings and the generalizability of finding. Thus, to avoid any sampling error. Besides that, the researcher also recommended to use the other method of gathering information such as interview and observation to strengthen the finding of the research. Avoid any use jargon words and use the simple word to easily respondent understand and answer the questionnaire. Last but not least, if possible, try to conduct the research with other different question about spending habits to view the result from different angles.